The Legacy of Desegregation: The Struggle for Equality in Higher Education - Maples, Rebeka L.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
The book analyzes the struggle of African Americans to gain access and equity in higher education in the United States. It chronicles some of the history prior to court ordered segregation and traces the mandate to desegregate by following the Adams v. Richardson (1973) case, which ordered the dismantling of dual systems of higher education.
Keywords: Science; Science; Science, general